Kadar Zat Gizi Makro pada Sagu (Metroxylon sagu) dan Tingkat Penerimaan Warna, Aroma, Rasa, Tekstur dan Kekenyalan Sinonggi sebagai Pangan Lokal bagi Penderita Diabetes Mellitus Tipe 2 - Ananda, Siti Hadrayanti; Abadi, Ellyani; Hasrima, Hasrima (Universitas Batanghari Jambi, 2025)
The aim of this research is to analyze the macronutrient content of local food (Sinonggi) and identify the level of acceptability (color, taste, smell, texture and crunchiness) of Sinonggi. This type of research is descriptive, with a total of 20 panelists. Data on the nutritional content of Sago was measured using the acceptance level using the Likert scale hedonic test. The results of this research found that Sago has a higher carbohydrate content than protein and fat, and the Sinonggi that many people like is Sinonggi S3.